Procalcitonin as prognostic factor in patients with Fournier's gangrene. Issue 1 (February 2023) - Ongaro, Luca; Claps, Francesco; Rizzo, Michele; Di Cosmo, Giacomo; Traunero, Fabio; D'Andrea, Eugenia; Garaffa, Giulio; Cai, Tommaso; Zucchi, Alessandro; Trombetta, Carlo; Liguori, Giovanni
Introduction: Fournier's Gangrene (FG) has still a mortality rate up to 45%. Several studies identified prognostic factors but there is a knowledge gap concerning procalcitonin (PCT) levels and mortality risk in FG. This study is aimed to assess the role of PCT as prognostic factor in FG. Materials and methods: The medical records of 20 male FG patients admitted at the Department of Urology of "Cattinara" Hospital, University of Trieste between January 2019 and November 2020 were retrospectively reviewed. Clinical, demographic, microbiological data were collected. The Fournier's Gangrene Severity Index (FGSI) was calculated for each patient. Results: Thirteen (65%) of 20 patients survived. Median age was 58 years (IQR 51–88), 15 patients (75%) had a Charlson Comorbidity Index (CCI) score ⩾2, 1 (5%) equal to 0, 4 to 1 (20%). Median FGSI score was 6 (IQR 2–12) and median PCT 0.8 ng/ml (IQR 0.04–2.12). At multivariate analysis PCT levels >0.05 ng/ml were associated with an increased overall mortality risk (OR 2.14, CI 1.25–4.27, p  = 0.002). CCI score ⩾2 (OR 1.51, CI 1.01–2.59, p  = 0.04), Streptococcical etiology (OR 3.41, CI 2.49–4.61, p  = 0.002) and FGSI score >9 (OR 1.41, CI 1.19–2.21, p  = 0.004) were associated with unfavorable outcome. Conclusion: PCT might be a prognostic factor in FG. CCI and FGSI are useful tools in mortality risk stratification. Streptococcical etiology is associated with unfavorable outcome. Further larger clinical trials are pending.